Aplikasi Monitoring Gangguan Frekuensi Radio Berbasis Android Menggunakan Firebase Cloud Messaging (FCM) - Manurung, Reni; Aspriyono, Hari; Prasetiyo, Eko (MEANS (Media Informasi Analisa dan Sistem), 2022)
This era is a very strategic resource in the digital era because many devices are connected using radio frequencies. The existence of these improvements requires managers who are responsible for managing the radio frequency spectrum against disturbances that occur to be more responsive and responsive. The need for information on disturbances flexibly between those in charge in the field and in the non-field must be real-time. There is a notification technology created by Google called Firebase Cloud Messaging (FCM). The FCM has the advantage of being a provider of information to field and non-field personnel regarding new disturbances that require the involvement of application users. This advantage is expected to make the person in charge to be responsive in dealing with disturbances. Therefore, the Android-Based Radio Frequency Interference Monitoring Application can assist in handling frequency disturbances from the reporter in real time and the reporting party will also easily get notifications and reports in real time.